223k views
3 votes
If f(x) = 4x - 6 and g(x) = √ x+2,
what is (fºg)(7)?

2 Answers

3 votes

Answer:

6

Explanation:

Evaluate g(7) then substitute this value into f(x), that is

g(7) =
√(7+2) =
√(9) = 3, then

f(3) = (4 × 3) - 6 = 12 - 6 = 6

User Yomotsu
by
5.1k points
5 votes

Answer:

6

Explanation:

f(x) = 4x - 6

g(x) = √ x+2

so we have that:

(fºg)(x) = 4( √ x+2)- 6

(fºg)(7) = 4( √ 7+2)- 6

(fºg)(7) = 4( √ 9)- 6

we know: √ 9 = √ 3^2 = 3

we have:

(fºg)(7) = 4(3)-6

(fºg)(7) = 12-6

(fºg)(7) = 6

User Mecho
by
4.6k points